Auditory Learning Styles and Their Impact on EFL Learners' Listening Proficiency - Irham Mifta Jannah; Risma Rahajeng Lestari; Sinta Restu Ningsih (Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates the influence of auditory learning preference on students’ listening proficiency. Although learning style inventories, particularly auditory learning preferences, have long been promoted as useful tools for improving language instruction, recent empirical evidence has questioned their ability to predict academic achievement. Most previous studies have focused on students’ perceptions of learning styles or their relationship with general learning outcomes, while relatively few have specifically examined whether auditory learning preference predicts listening proficiency in English as a Foreign Language (EFL) context. Addressing this gap, the present study employed a quantitative approach involving 22 auditory-dominant students. Data were analysed using descriptive statistics and Simple Linear Regression. The results revealed that auditory learning preference was not a statistically significant predictor of listening proficiency (*p* = 0.460 0.05), explaining only 2.8% of the variance in students’ listening scores. These findings suggest that self-reported auditory learning preference is not a reliable predictor of listening success. The study highlights the importance of prioritizing evidence-based instructional approaches, including vocabulary development and metacognitive listening strategies, rather than relying on learning style classifications. These findings contribute to the growing body of research challenging the educational value of learning style inventories in second language acquisition.